Development of position tracking electric drive system to control BLDC motor working in very low mode for industrial machine application - Pham Van Minh; Tran Duc Chuyen; Dang Quoc Du; Hoang Dinh Co (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In this paper, the research and development of kinematic characteristics and models of electromechanical tracking drive systems working in slow mode are presented, applied in industrial, civil, national defense and security machines security, using brushless direct current motors (BLDC). On the basis of building simulation models; then evaluate the speed, rotation angle, torque, and current components for this tracking electric drive system. The simulation model was verified on MATLAB/Simulink, experimented with the model to demonstrate the research results. These research results will be the basis for setting up control algorithms and designing tracking electric drive systems in industry, civil and national defense.